2007
DOI: 10.1186/1476-9255-4-11
|View full text |Cite
|
Sign up to set email alerts
|

CXC-chemokine regulation and neutrophil trafficking in hepatic ischemia-reperfusion injury in P-selectin/ICAM-1 deficient mice

Abstract: Background: Neutrophil adhesion and migration are critical in hepatic ischemia and reperfusion injury (I/R). P-selectin and the intercellular adhesion molecule (ICAM)-1 can mediate neutrophilendothelial cell interactions, neutrophil migration, and the interactions of neutrophils with hepatocytes in the liver. Despite very strong preclinical data, recent clinical trials failed to show a protective effect of anti-adhesion therapy in reperfusion injury, indicating that the length of injury might be a critical fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Crockett et al [49] recently showed that significant neutrophil infiltration can occur in P-selectin and ICAM-1 null mice, suggesting that alternative adhesion recruitment pathways independent of adhesion molecule expression do exist and can participate in neutrophil migration during an inflammatory response. Additional studies in mice have indicated that while adhesion molecules are important modulators of neutrophil infiltration, the mode of stimuli and duration of the injury can modulate neutrophil infiltration via the expression of chemotactic cytokines or CXC-chemokines, such as interleukin-8 (IL-8), that may play an equally central role in recruitment and migration [50]. Further studies supporting the importance of chemokines in leukocyte recruitment into inflamed ileal pouch tissue of CUC patients who have undergone IPAA demonstrated that the expression of monocyte chemotactic protein-1 and 3, as well as IL-8, were significantly elevated during episodes of acute ileal inflammation compared with the normal pouch ileum [51].…”
Section: Discussionmentioning
confidence: 99%
“…Crockett et al [49] recently showed that significant neutrophil infiltration can occur in P-selectin and ICAM-1 null mice, suggesting that alternative adhesion recruitment pathways independent of adhesion molecule expression do exist and can participate in neutrophil migration during an inflammatory response. Additional studies in mice have indicated that while adhesion molecules are important modulators of neutrophil infiltration, the mode of stimuli and duration of the injury can modulate neutrophil infiltration via the expression of chemotactic cytokines or CXC-chemokines, such as interleukin-8 (IL-8), that may play an equally central role in recruitment and migration [50]. Further studies supporting the importance of chemokines in leukocyte recruitment into inflamed ileal pouch tissue of CUC patients who have undergone IPAA demonstrated that the expression of monocyte chemotactic protein-1 and 3, as well as IL-8, were significantly elevated during episodes of acute ileal inflammation compared with the normal pouch ileum [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, the concentration of MDA was obviously lower in the melatonin exposure group than in the other two control groups 6, 12 and 24 h after reperfusion, indicating that melatonin can relieve the IR injury by eliminating free radicals [22] . It was reported that ICAM-1 is directly correlated with the inflammation of white blood cells and vascular endothelial cells [23] . In this study, ICAM-1 gradually increased after reperfusion and decreased after reaching its peak between 12 and 24 h, which was in accordance with the concentration of TNF-α in systemic circulation.…”
Section: Applicationsmentioning
confidence: 99%
“…It’s possible that KC receptors are not up regulated in the skeletal muscle of the non hypercholesterolemic C57BL6 mice so that KC synthesized in the skeletal muscle of mice subjected to demand ischemia could be released into the systemic circulation. While there is substantial data to support KC release from exercised muscle (35, 36), it is also possible that the KC detected in plasma of the C57BL6 mice subjected to demand ischemia was synthesized by cells outside the ischemic limb.…”
Section: Resultsmentioning
confidence: 99%